Climate Change as Climate Debt: Forging a Just Future - Moe-Lobeda, Cynthia D. (Journal of the Society of Christian Ethics, 2016)
Climate change may be the most far-reaching manifestation of white privilege and class privilege to face humankind. Caused overwhelmingly by high-consuming people, climate change is wreaking death and destruction foremost on impoverished people, who also are disproportionately people of color. This essay first posits climate change as a compelling moral matter of race- and class-based climate debt and Global North climate debt. A second part draws upon the descriptive and transformative tasks of Christian ethics as a critical discourse to frame a moral response. Finally, the essay illustrates implications for public policy. I propose the concepts of climate privilege, climate violence, and blinders of climate privilege as tools for demystifying our situation; climate reparations as a dimension of a moral response; and atmospheric citizenship as a tool for moral identity